Fabrication of large-area silicon nanowires arrays for solar cell application - Leow, Yan Xiang. (2010)
The technical compatibility of forming nanopillars with existing semi-conductor technology will be used to fabricate large area silicon nanowires array for solar cell device. The nanopillars on the solar cell has many advantages in term of light trapping, shorter distance for photon generated carriers collection, cost and efficiency than existing solar cell with multiple antireflection coatings and surface texturing. So the purpose of the project is to fabricate the periodically aligned silicon nanopillars, the disordered silicon nanopillars and the planar solar cell where their power conversion efficiency and the reflectance are examined and compared. From the discussion, the silicon nanopillars are achieved using silver catalyzed wet chemical etching method where the periodically aligned silicon nanopillars with a controllable length, diameter and density would use PS sphere as a mask to achieve highly ordered nanopillar to achieve light reflection suppression and enhanced light trapping. It also has shorter distance for photon generated carrier collection and thus increases the power conversion efficiency of the solar cell. The power conversion efficiency of the periodically aligned silicon nanopillars is found to be the best among the 3 solar cell. Therefore we can conclude that the periodically aligned silicon nanopillars with a highly order nanopillars is the most promising in term of light trapping, shorter distance for photon generated carriers collection and power conversion efficiency. However, much research can be done to further improve its efficiency by optimizing the electrical contact and the manufacturing defect on the PN junction. Also by varying the sequence of the process, the vertical aligned core-shell silicon nanopillars solar cell could be look into to produce a higher efficiency solar cell.